2015
DOI: 10.1155/2015/293053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serine Proteases and Antiproteases in the Cystic Fibrosis Lung

Abstract: Cystic fibrosis (CF) lung disease is an inherited condition with an incidence rate of approximately 1 in 2500 new born babies. CF is characterized as chronic infection of the lung which leads to inflammation of the airway. Sputum from CF patients contains elevated levels of neutrophils and subsequently elevated levels of neutrophil serine proteases. In a healthy individual these proteases aid in the phagocytic process by degrading microbial peptides and are kept in homeostatic balance by cognate antiproteases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 128 publications
(145 reference statements)
2
72
0
1
Order By: Relevance
“…2B). The WT-level growth of the SSVR mutants might argue against the importance of S1/S2 cleavages in HAE infections; however, we note that HAE are frequently collected from patients with underlying pulmonary diseases (e.g., chronic obstructive pulmonary disease, cystic fibrosis, pulmonary fibrosis, α-1 antitrypsin deficiency), conditions associated with increased levels of mucus-associated proteases (40)(41)(42). Airway mucus-associated proteases are known to cleave SARS-CoV S proteins (43), and therefore we suggest that the SSVR mutant MERS-CoVs are similarly cleaved by extracellular proteases, making their infection resemble that of WT viruses at the point of entry into some HAE cells.…”
Section: Discussionmentioning
confidence: 95%
“…2B). The WT-level growth of the SSVR mutants might argue against the importance of S1/S2 cleavages in HAE infections; however, we note that HAE are frequently collected from patients with underlying pulmonary diseases (e.g., chronic obstructive pulmonary disease, cystic fibrosis, pulmonary fibrosis, α-1 antitrypsin deficiency), conditions associated with increased levels of mucus-associated proteases (40)(41)(42). Airway mucus-associated proteases are known to cleave SARS-CoV S proteins (43), and therefore we suggest that the SSVR mutant MERS-CoVs are similarly cleaved by extracellular proteases, making their infection resemble that of WT viruses at the point of entry into some HAE cells.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it may also be beneficial to design targeted interventions aimed at optimizing airway macrophage function in children with CF (56). Understanding the fate of extracellular NE is critical to correct the protease-antiprotease imbalance that characterizes CF airways (57). However, targeting NE may not suffice, because similar complex activation and compartmentalization may occur with other proteases, such as matrix metalloproteinases 2, 9, and 12, which originate from neutrophils and macrophages (46,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…HAT in the upper respiratory tract. Previous investigations have demonstrated that serine proteases participate in the pathogenesis of inflammation, infection, and fibrotic processes in the airways and lung (5,10,17,28,31,42,49,62,113,141,144,150). We recently demonstrated the implication of matriptase in idiopathic pulmonary fibrosis (IPF) (10) through its activation of PAR-2.…”
Section: Hat and Fetal Developmentmentioning
confidence: 99%
“…The catalytic site of HAT (blue box) includes the catalytic triad His 227 , Asp 272 , and Ser 368 . Potential N-linked glycosylation sites, Asn-Asn-Ser and Asn-Pro-Ser at Asn144 and Asn 152 (diamond-headed arrows), are located on the boxed SEA domain. Four disulfide bonds are located in the extracellular region, at cysteine pairs 212/228, 337/353, and 364/393 in the catalytic region and at 173/292 between the noncatalytic region and the catalytic region.…”
mentioning
confidence: 99%